Esquirol, Josep Maria. La resistencia íntima. Ensayo de una filosofía de la proximidad. Barcelona: Acantilado, 2015; 178 p. (2016)
Esquirol, Josep Maria. La resistencia íntima. Ensayo de una filosofía de la proximidad. Barcelona: Acantilado, 2015; 178 p.